Characterisation of hexon and fibre genes of a novel strain of adenovirus involved in epidemic keratoconjunctivitis. Issue 1 (23rd December 2003) - Adhikary, A K; Inada, T; Numaga, J; Suzuki, E; Ushijima, H; Banik, U; Mukouyama, A; Matsuno, S; Okabe, N
Abstract : Aims: To characterise a novel strain (M86) of adenovirus (Ad) involved in epidemic keratoconjunctivitis (EKC). Methods/Results: The virus strain was neutralised by antisera to both Ad35 and Ad11. Restriction endonuclease analysis of genomic DNA showed 98% and 88% homology with Ad11 and Ad35, respectively. The deduced amino acid sequence of the hypervariable regions of (HVRs) of the hexon gene showed a higher homology with Ad35 (94.4%) than with Ad11 (83.7%). However, it was 100% homologous to Ad35 in HVRs 1, 2, 3, and 6 and to Ad11 in HVRs 4 and 6. In the fibre knob, the isolate was more homologous to Ad11 (99.4%) than to Ad35 (29.1%). Conclusion: This novel strain of adenovirus showed similarities with both Ad11 and Ad35. The isolation of a novel strain like Ad35+11 is important because of its association with EKC.